Detection of antibiotic waste in raw milk, pasteurized and Ultra High Temperature (UHT) commercialized in Unaí, Minas Gerais (Research, Society and Development, 2020)
Milk quality can be evaluated by physical-chemical, sensory, microbiological parameters and by the presence of chemical residues, such as antimicrobial. The main source of these substances in the milk is a consequence is the inadequate management of medications aimed at the control of illness in the herd, breach of the milk dispose during the grace period and flaws in utensils and equipment hygiene. The aim of this study is to evaluate raw-milk, pasteurizes and UHT milk quality commercialized in Unaí-MG under surveillance of inspection services or informally commercialized, in relation to the presence of antibiotic residues. 56 milk samples were analyzed, being 16 of raw-milk, 16 of pasteurized milk and 24 of UHT milk (8 sample of whole milk, 8 samples of semi-skimmed milk and 8 samples of skimmed milk) using the IDEXX SNAP® duo™ ST Plus kit. After the accomplishment of analytical tests, it was possible to verify that pasteurized and UHT samples did not contain antibiotic residues tested, while just one raw-milk sample presented positive for the presence of β-lactam residues. These results show the necessity of the compliance of grace period during the treatment of livestock as well as the necessity to control antimicrobial residues on the dairy industry reception platform beyond the surveillance by the Official Inspection Service aimed at the production of innocuous food.